Oral Health Status, Oral Health Care And Dietary Practices Of Special Needs Children - Al-Sanabani, Amal Ali Mohammed (2011)
Oral health is multifactorial. Children with special health care needs are at greater risk for poorer oral health than normal children Objectives: This study aimed to determine the prevalence of dental caries, periodontal disease, oral hygiene status and oral health care practices and dietary practices and explore its associations among special needs children. Methodology: This cross-sectional descriptive study involved 125 special needs school children in Kota Bharu district. DMFT, CPI and OHI-S indices were used to evaluate caries experience, periodontal status and oral hygiene status respectively. Dental examination was done on portable dental chair with portable light and mobile dental bus equipped with dental chair and lighting.